2009
DOI: 10.1186/ar2794
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of radiographic progression in the spines of patients with ankylosing spondylitis treated with adalimumab for up to 2 years

Abstract: Introduction Ankylosing spondylitis (AS) is a chronic rheumatic disease associated with spinal inflammation that subsequently leads to progression of structural damage and loss of function. The fully human anti-tumor necrosis factor (anti-TNF) antibody adalimumab reduces the signs and symptoms and improves overall quality of life in patients with active AS; these benefits have been maintained through 2 years of treatment. Our objective was to compare the progression of structural damage in the spine in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
194
2
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(214 citation statements)
references
References 31 publications
10
194
2
8
Order By: Relevance
“…An alternative hypothesis was then proposed whereby pathogenetic factors such as altered gene expression, biomechanical factors, and bacteria trigger the concomitant expression of inflammation and new bone formation, which then proceed along essentially autonomous pathways (2). This hypothesis has been advanced to explain the apparent lack of benefit of anti-TNF␣ agents on the radiographic progression of AS (3)(4)(5).…”
mentioning
confidence: 99%
“…An alternative hypothesis was then proposed whereby pathogenetic factors such as altered gene expression, biomechanical factors, and bacteria trigger the concomitant expression of inflammation and new bone formation, which then proceed along essentially autonomous pathways (2). This hypothesis has been advanced to explain the apparent lack of benefit of anti-TNF␣ agents on the radiographic progression of AS (3)(4)(5).…”
mentioning
confidence: 99%
“…El bloqueo farmacológico con agentes anti TNFalpha en EA controla la inflamación y reduce la extensión del edema de médula ósea por hallazgos en RMN, pero el control de la erosión ósea en la entesis es menos consistente en particular la formación de sindesmofitos 13 . Lo anterior sugiere que dichos procesos no se encuentran completamente acoplados a la inflamación o asociados a factores destructivos específicos de hueso 14 .…”
Section: Factores Destructivos De Huesounclassified
“…Estos hallazgos confirman que el patrón de erosión en EA caracterizado por exceso de formación ósea perióstica, difiere del proceso observado en AR. Así mismo, se correlaciona con los resultados de estudios clínicos en los cuales el bloqueo anti TNF-alpha es menos efectivo para detener el proceso de erosión en comparación con AR 13,14 . Por lo tanto, el impacto del proceso inflamatorio en el hueso es específico de su localización, tipo celular involucrado, citocinas y factores presentes en el microambiente local 19 .…”
Section: Destrucción Vs Neoformaciónunclassified
“…The goal of treatment of axial SpA is to obtain the suppression of symptoms but also the prevention of structural bone damage and of ankylosis. The studies on anti-TNF agents in longstanding axial disease have demonstrated that the structural damaged cannot be prevented and that it is independent from the presence of absence of inflammatory activity (13)(14)(15). A great effort should be done to increase the referral of every axial SpA patient to the rheumatologist.…”
mentioning
confidence: 99%